Moral Education of Children in the Lithuanian Peasant Families in the First Half of the20th Century: Ethno-Pedagogic Qualitative Analysis - Stonkuvienė, Irena (Acta Paedagogica Vilnensia, 2000)
In present work the reality of education in the Lithuanian peasant families is analysed in the first half of the XX century in terms of retrospective understanding of the participants of the educational process. It also examines the particularities of how the concrete conditions in the family, and the age and sex of the children affected the content, principles, and methods of education.
Keywords: Moral education; ethno - pedagogy; family; rural community.